Assessment of Arabic Language Learning According to the New Revised Curricula in the Primary Education Stage - maatoug, mohamedlamine; salmi, Karima (El Omda in Linguistics and Discourse Analysis, 2023)
Summary: This study aims to shed light on evaluating the learning process in the Arabic language curricula through the reforms brought about by the new curricula rewritten in the primary education stage, being the curricula the main means to ensure the achievement and development of the educational process as a whole, in keeping with all educational developments and investment in technological formation. the individual. In the beginning, we preferred to stand on the evaluation mechanisms that these curricula came with. We dealt with these mechanisms in some analysis and detail. The study focused on what it deems most important in the success of learning the Arabic language in all its branches, which is the field of understanding the spoken text the spoken text. Quality in the evaluation Focus on the operative. This is by answering the problem posed, adopting the descriptive approach appropriate to the nature of the study